PENGARUH GAYA KEPEMIMPINAN KEPALA PUSKESMAS TERHADAP KINERJA TENAGA KESEHATAN DI PUSKESMAS PEUREULAK BARAT - Usman Usman; Muhammad Badiran; Iman Muhammad (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2020)
Today leadership is at the core of economic development in the Asian region including Indonesia. There are two dominant leadership styles, namely American (western) leadership style, and Asian (eastern) leadership style. Based on the preliminary survey conducted, it was seen that the style used by the leaders was the interaction of the leader with his subordinates, but the style was not used well so that it was seen in 10 health workers in West Peureulak Health Center, 6 of whom had low performance. The purpose of this study was to determine the effect of the leadership style of the puskesmas head on the performance of health workers at the Peureulak Barat Health Center in East Aceh Regency in 2018.The research design used in this study was Cross Sectional. The population in this study were 52 health workers and samples taken by total sampling were as many as 51 health workers. Methods of data collection are primary data and secondary data. Data analysis used is binary logistic regression test.The results showed that transactional leadership style had a sig-p value of 0.016 <0.05, transformational sig-p .005 < .05 and situational leadership style had a sig-p value of .003 < .05, which means that all leadership styles have an influence on quality health services, while caring does not have an influence on the performance of health workers.The conclusion in this study is the influence of transactional, transformational and situational leadership styles on the performance of health workers. It is hoped that it can become a reference for the community and for cadres in the Puskesmas to better understand the importance of appropriate leadership styles to maximize the performance of health workers to the fullest.Keywords : leadership style, performance, transactional, transformational, situational